Perancangan Sistem Informasi Pelacakan Alumni Pada Program Studi Sistem Informasi Berbasis WEB - Irawan, Yudie; Muzid, Syafiul; Puspitasari, Dwi (Jurnal Sains dan Teknologi, 2014)
The  research  discusses  the  development  of  alumni  tracking  system  using  a  web-based  information technology.  Development  of  the  sistem  using  Waterfall  model.  At  the  planning  stage  researchers collected  data  from  studies  program  manager  of  alumni,  alumni  data  from  several  faculty  and administrative data collection directly from the alumni. Those data used by researcher to analyze the proposed  alternative  system  requirement  at  the  analysis  phase.  At  the  design  stage  researchers  to develop alternative systems chosen to make the system design and database design. Researchers using the Unified Modeling Language (UML) in the presentation of system design and database design. The final  stage  is  the  implementation  of  a  design  to  a  form  web  based  application.  Researchers  using Hypertext Preprocessor (PHP) in building the system and the MySQL database in the development of physical database. The  system  is  based  website  "tracer  study"  which  focused  on  the  management  of  information  about graduates waiting period, the percentage amount of graduates who are already has a job, and earning first  graduates,  as  well  as  obtain  information  about  possible  deficiencies in  the educational  process and the learning process. In addition to the web this is presented in tabular form is also presented in the form of three-dimensional graphics. The weakness of this research is the lack of research on the system security.